2016
DOI: 10.21608/jfds.2016.42817
|View full text |Cite
|
Sign up to set email alerts
|

Making Kareish Cheese With High With Added Sesame Hulls

Abstract: Kareish cheese was made from skimed buffalo's milk fortified with 1%, 2%, 3%, 4% and 5% sesame hulls. Control cheese and their treatments were stored for three weeks at 5• respectively C. The chemical composition, microbiological and organoleptic properties were determined in cheese and its treatments weekly. The results showed that moisture and fat were decreased, protein, ash, fiber and vitamin A contents increased with increasing the amount of sesame hulls, while the pH value and soluble nitrogen (SN) decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Incorporation of DSP and OP decreased insignificantly fat and fat on dry matter. These results are in agreement with El-Sayed et al (2016), who showed that increasing the amount of sesame hulls in Kareish cheese made from skimmed buffalo's milk fortified with 1%, 2%, 3%, 4% and 5% sesame hulls decreased fat. From the same Table it could be also noticed that salt and salt in moisture contents in all cheese treatments gradually increased during storage period with no pronounced differences due to the applied treatments.…”
Section: Resultssupporting
confidence: 92%
“…Incorporation of DSP and OP decreased insignificantly fat and fat on dry matter. These results are in agreement with El-Sayed et al (2016), who showed that increasing the amount of sesame hulls in Kareish cheese made from skimmed buffalo's milk fortified with 1%, 2%, 3%, 4% and 5% sesame hulls decreased fat. From the same Table it could be also noticed that salt and salt in moisture contents in all cheese treatments gradually increased during storage period with no pronounced differences due to the applied treatments.…”
Section: Resultssupporting
confidence: 92%
“…The chemical composition of kareish cheese is in agreement with those of Ghada et al, (2004), and Awad et al, (2015) and El-Sayed et al, (2016). The result of rice flour chemical compostion was in agreement with those of Turabi et al, (2008).…”
Section: Chemical Composition Of Raw Materials Used In Preparationsupporting
confidence: 90%
“…These results might be due to the increase in protein content occurred in all treatments with all concentrations. Statistically, there were significant differences by the increase of functional foods under study addition and between the samples by the increasing of storage period (El-Sayed et al, 2016).…”
Section: Chemical Composition Aciditymentioning
confidence: 84%